Tectonic, paleoclimate, and paleoceanographic history of high-latitude southern margins of Australia during the Cretaceous - Huber, Brian T.; Hobbs, Richard W.; Bogus, Kara A.; Batenburg, Sietske J.; Brumsack, Hans-Jürgen; Do Monte Guerra, Rodrigo; Edgar, Kirsty M.; Edvardsen, Trine; Harry, Dennis L.; Hasegawa, Takashi; Haynes, Shannon J.; Jiang, Tao; et al. (IODP-MI, 2018)
The tectonic and paleoceanographic setting of the Great Australian Bight (GAB) and the Mentelle Basin (MB; adjacent to Naturaliste Plateau) offered an outstanding opportunity to investigate Cretaceous and Cenozoic climate change and ocean dynamics during the last phase of breakup among remnant Gondwana continents. Sediment recovered from sites in both regions during International Ocean Discovery Program Expedition 369 will provide a new perspective on Earth's temperature variation at sub-polar latitudes (60°-62°S) across the extremes of the mid-Cretaceous hot greenhouse climate and the cooling that followed. The primar y goals of the expedition were to • Investigate the timing and causes for the rise and collapse of the Cretaceous hot greenhouse climate and how this climate mode affected the climate-ocean system and oceanic biota; • Determine the relative roles of productivity, ocean temperature, and ocean circulation at high southern latitudes during Cretaceous oceanic anoxic events (OAEs); • Identify the main source regions for deep-water and intermediate-water masses in the southeast Indian Ocean and how these changed during Gondwana breakup; • Characterize how oceanographic conditions at the MB changed during the Cenozoic opening of the Tasman Passage and restriction of the Indonesian Gateway; • Resolve questions on the volcanic and sedimentary origins of the Australo-Antarctic Gulf and Mentelle Basin and provide stratigraphic control on the age and nature of the prebreakup successions. Hole U1512A in the GAB recovered a 691 m thick sequence of black claystone ranging from the early Turonian to the early Campanian. Age control is primarily based on calcareous nannofossils, but the presence of other microfossil groups provided consistent but low-resolution control. Despite the lithologic uniformity, longand short-term variations in natural gamma ray and magnetic susceptibility intensities show cyclic alternations that suggest an orbital control of sediment deposition that will be useful for developing an ...